Persistence and Adherence to Biologics in Patients with Psoriasis in Taiwan: A New Biologics User Cohort Study - Huang, Yu-Huei; Tang, Chao-Hsiun; Goh, Choo Hua; Chang, Chia-Li; Qiu, Hong; Yang, Ya-Wen; Saadoun, Carine; Chang, Chia-Ling; Liu, Yanfang (Frontiers in Pharmacology, 2022)
Background: Biologics are used to treat moderate-to-severe psoriasis, and persistence to biologics may reflect clinical effectiveness. Limited information describing how biologics are used in patients with moderate-to-severe psoriasis in Asian countries is available. We conducted a population-based, retrospective, new user cohort study using the National Health Insurance Research Database (NHIRD) in Taiwan to assess treatment persistence and adherence to biologics. Methods: Adults with a diagnosis of psoriasis between 01 January 2015 and 31 December 2017 were identified in the NHIRD (ICD-9-CM 696.1; ICD-10 L40.0). New users were patients who initiated treatment with etanercept, adalimumab, ustekinumab or secukinumab between 01 January 2015 and 31 December 2017. All eligible patients were followed until 31 December 2018, death or disenrollment. Kaplan-Meier analysis was conducted to estimate persistence of treatment for index biologics. A Cox-proportional hazard regression model was used to compare risks of biologic discontinuation between biologic groups. Adjustments for potential confounding factors (age, gender and Charlson comorbidity index score) were made in the Cox model. Results: There were 1397 new biologic users with psoriasis during the study period. The ratio men:women was approximately 4:1. Mean age of patients ranged from 44.6 to 47.7 years across exposure groups. The 1-year/2-year persistence rates were 94.2%/84.9% for ustekinumab, 96.2%/not calculated (due to too few patients at year 2) for secukinumab, 66.0%/29.9% for etanercept, and 59.8%/40.3% for adalimumab. The risk of discontinuation was significantly lower in patients initiating ustekinumab compared with adalimumab (hazard ratio adjusted for age, sex and co-morbidities 0.289, 95%CI 0.247-0.339, p<0.0001). Drug survival was significantly higher for ustekinumab compared with adalimumab and etanercept (log-rank test p<0.0001). The proportions of patients with 1-year/2-year medication possession ratios of ≥80% were 95.3%/92.0% for ustekinumab, 98.1%/not calculated for secukinumab, 89.4%/83.1% for etanercept, and 70.8%/59.4% for adalimumab. Limitations: Clinical improvement and response to treatment data were not available. Conclusion: There was relatively high persistence amongst biologic users with psoriasis in Taiwan. There is a trend towards greater persistence of ustekinumab compared to other biologics, the magnitude of which depends on the treatment gap used for its calculation. This study provides real-world evidence that may facilitate optimal treatment choice.